AN ANALYSIS OF PLANT NURSERY BUSINESS AND PRODUCTION RESOURCES IN TWIN CITIES OF TELANGANA - NEELA RANI, J. DEEPIKA, P. RADHA RANI, V. VIJAYALAKSHMI and (The Journal of Research, PJTSAU, 2019)
Plant nursery sector is playing an important role in the country after agriculture in providing self-employment to the youth. It also contributes in protection of the environment. The purpose of the study was to gather information regarding plant nurseries. A total number of 25 plant nurseries were selected through purposive random sampling technique. Data was analyzed by using Microsoft Excel 2010. Frequencies and percentage were performed to detect the statistical significance. Results revealed that majority (40%) of the plant nurseries were forestry developed under open spaces (56%) by taking a rented land (48%) within 0.51-1.0 hectares of land and engaged both wife and husband (60%) in different activities of plant nursery. Nearly half percentageof plant nurseries were using polythene bag method and inorganic manure for the growth and development of seedlings. Forty per cent of the sampled nurseries were private established by taking loans from bank and from government sponsors, providing gardening services and sales were done through contract.